An investigation into the impact of enteric coated of aspirin in patients with newly diagnosed ischemic stroke (ECASIS). Issue 20 (15th May 2020) - Elshafei, Mohamed Nabil; Imam, Yahia; Mohamed, Mouhand F.H.; AlSaud, Arwa Ebrahim; Ahmed, Mohamed Sayed; Obeidat, Khaldun; Saeid, Razan; Ali, Mohamed; Abdallah, Ibtihal M.; Parray, Aeijaz Sultan; Danjuma, Mohammed Ibn-Masoud
Abstract: Introduction: Uncertainty remains regarding the impact of enteric-coated (EC) aspirin as it relates to the reduction of cardiovascular risk. We hypothesize that EC formulation based on a previous report may blunt aspirin response as evidenced by reduced Thromboxane A2 (TXA 2) levels in diabetic patients. Thus, it was imperative to ascertain and validate the effect of the EC formulation of Aspirin on the Thromboxane B2 (TXB2) level. Methods/design: An open-label consecutive randomized interventional controlled trial. Patients with newly diagnosed ischemic stroke who are just about to start Aspirin were assessed for eligibility and inclusion in our trial. Consecutive patients (admitted to the stroke unit of Hamad General Hospital, Hamad Medical Corporation, Doha, Qatar) will be randomized to receive either EC aspirin or plain Aspirin. They will be required to continue taking them throughout the study (3 days). Demographics and laboratory records of the study participants will be abstracted from online records. Further study variables will be obtained manually in designated case record forms (CRF). The primary outcomes are the incidence of aspirin non-responders (level of residual serum TXB2 associated with elevated thrombotic risk (<99.0% inhibition or TXB2 >3.1 ng/mL) within 72 h after three daily aspirin doses). Whereas secondary outcomes are the incidence of GIT bleeding of various preparations of Aspirin. The study was approved by MRC and IRB of Hamad Medical Corporation (MRC number: 01-18-156). Discussion: This trial will determine potential differences in the efficacy of EC Aspirin and plain Aspirin on the Thromboxane B2 level. Additionally, it will ascertain the tolerability and safety of both formulations of Aspirin in patients with newly diagnosed ischemic stroke. These results will either support the current notion of no difference between the two formulations. However, if a difference is found, this will invite for future trials exploring clinical outcomes occurrence between various formulations. Clinical trial registration: Clinicaltrials.gov NCT04330872 registered on April 2, 2020 Abstract : Supplemental Digital Content is available in the text